Reasons why self-referring patients attend the emergency department during daytime differ among socioeconomic groups: A survey from Flanders. (1st January 2018) - Detollenaere, Jens; Boucherie, Julie; Willems, Sara
Abstract: Background: Numerous studies have shown that during out-of-hours vulnerable patients (regarding low-education and unemployment) are more likely to seek medical help in the emergency department (ED). However, little is known about why patients seek help in the ED during daytime hours and if these reasons differ among self-referring socioeconomic groups. Objectives: To identify the reasons why patients opt for the ED during daytime hours when primary care services are available and identify possible social differences between socioeconomic groups. Methods: In 2014–2015, trained fieldworkers surveyed 723 patients visiting four EDs in Flanders using a structured interview. These quantitative data were analysed using descriptive and logistic regression analyses. Results: More than one-third of the self-referring patients reported that they attend the ED during daytime hours because they perceive their (health) problem as urgent and expect they need advanced diagnostic testing. Self-referred and low-educated patients have a 1.8 higher chance (compared to their higher-educated counterparts) of attending the ED because they expect advanced diagnostic testing. Self-referred and unemployed patients have a 3.6, 2.5 and 4.4 higher chance (compared to their employed counterparts) to opt for the ED because it is their usual source of care, family/friends refer them or they postpone care too long, respectively. Conclusion: We found sociodemographic differences in motives why self-referring patients in Flanders opt for the ED during daytime hours. In general, self-referring patients attend the ED because they perceive their condition as urgent and think they may need advanced diagnostic testing.